AMERİKADA DEMOKRASİNİN GELİŞİMİ VE MAGAZİN GAZETECİLİĞİ: YEREL BASINDAN BİR ÖRNEK "THE DENVER POST" - Gürses, Fatma (NWSA Academic Journals, 2015)
Since its establishment, United States of America has contributed a lot to the literature and democracy struggle with its journalism practices. The yellow journalism practices can be considered as one of these acquisitions; and it began to be implemented since the appearance of press in America. This type of journalism has been a tool used by the local press to accommodate democracy. This study analyzes the “yellow journalism” implementations in the sample of The Denver Post, which had been effective in the Colorado state. This study has aimed to examine the journalism practices that play an important role in the development of democracy; with a focus of the concept “yellow journalism” in the democracy, local press and especially the American local press. For this reason, the study consisted of two chapters. The first chapter examines the concept of yellow journalism, and the characteristics of journalism practices along with the historical development of this concept. Second chapter evaluated The Denver Post, chosen as a sample from the American local press, and its effect in Colorado State, along with its contribution to American democracy. It is thought that the study will be a source for further studies on democracy, local press and journalism
Keywords: Yerel Basın; Magazin Gazeteciliği/Sarı Gazetecilik; Demokrasi; Amerika Birleşik Devletleri; The Denver Post.; Local Press; Yellow Journalism; Democracy; 4. Education